A Decade of Drinking: Temporal Trends in Apparent Household Beer Intake and Standard Drink Consumption in the United States. (29th July 2021) - Schiff, Mary D.; Mendez, Dara D.; Gary-Webb, Tiffany L.; Inman, J. Jeffrey; Fabio, Anthony
Abstract: Beer remains the greatest source of per capita alcohol consumption in the United States, and increasing market availability and consumer demand for higher alcohol has meaningful public health consequences. Objectives: To determine whether apparent alcohol intake from beer changed among households over time, we used nationally-representative US Nielsen Consumer Panel purchasing data from 2004 to 2014, and incorporated information on percent alcohol by volume (ABV) to compute the number of standard drinks of alcohol consumed from beer as a result. Methods: We queried external data sources (e.g. official manufacture, consumer beer-related websites) to obtain beer-specific ABVs, merged this information with Nielsen consumer-level data, and calculated the average rate of beer and standard drink consumption per household per year. We used joinpoint regression to estimate annual percentage changes and annual absolute changes in intake over time, with separate piecewise linear segments fit between years if a significant deviation in trend was detected. Results: Higher alcohol content beer consumption increased steadily across the decade, accounting for 9.6% of total intake in 2004 compared to 21.6% of total intake by 2014. Standard drink intake from beer declined sharply post-2011 by 3.04% annually (95% CI: −5.93, −0.06) or by 4.52 standard drinks (95% CI: −8.69, −0.35) yearly – coinciding with several beer industry transitions, market share fluctuations, and consumer preference changes for beer occurring around that time. Conclusions: Despite consistent increases in higher alcohol content beer intake across the decade, households do not appear to be consuming more standard drinks of alcohol from beer as a result. Supplemental data for this article is available online at https://doi.org/10.1080/10826084.2021.1928208 .